Reduced salivary flow and colonization by mutans streptococci in children with Down syndrome (Clinics, 2012)
OBJECTIVES: Although individuals with Down syndrome have considerable oral disease, the prevalence of dental caries in this group is low. The present study aimed to compare known risk factors for dental caries development in children with Down syndrome and a matched population (siblings). In both populations, the number of acidogenic microorganisms, such as mutans streptococci, lactobacilli and Candida species, and the paraffin-stimulated pH, flow rate and IgA concentration in whole saliva were evaluated and compared. METHOD: Saliva was collected, and the caries index was evaluated in 45 sibling pairs aged between 6 and 18 years old. The salivary IgA concentration was determined by immunoturbidimetry. Salivary mutans streptococci, lactobacilli and Candida species were quantified on mitis salivarius agar containing bacitracin and 20% sucrose, rogosa agar supplemented with glacial acetic acid and sabouraud agar supplemented with chloramphenicol, respectively. RESULTS: Down syndrome children had a higher caries-free rate (p